Implementation Of Web-Based E-Learning at The Faculty Economics Of The 1945 Teacher Union University Of NTT - Yunikentri Pramayshela Adu; Sumarlin; Bara, Bintang (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
In the digital area, the effectiveness of the knowledge sharing process is one of the main challenges, especially in the world of education. This research aims to design and build an E-Learning platform to support various knowledge in the Faculty of Economics, of Persatuan Guru 1945 University East Nusa Tenggara. This system is designed to make it easier for lecturers and students to access course materials, interact online, manage exams and assignments, and improve communication between lecturers and students. This research uses the waterfall software development method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The implementation of this system is expected to improve the efficiency of the knowledge sharing process at the Faculty of Economics, Persatuan Guru 1945 University East Nusa Tenggara, so that the resulting system can meet the needs of more efficient and effective learning.